2016
DOI: 10.3390/agriculture6020018
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practices towards Leptospirosis among Lakeshore Communities of Calamba and Los Baños, Laguna, Philippines

Abstract: Leptospirosis is a serious and potentially fatal zoonotic disease, but often neglected owing to lack of awareness. This study examined the knowledge, attitudes, and practices concerning leptospirosis among agricultural (n = 152) and non-agricultural (n = 115) workers in the lakeshore communities of Calamba and Los Baños, Laguna, Philippines. The findings showed no significant differences for the knowledge and attitude scores between agricultural and non-agricultural workers. However, agricultural workers had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
41
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 35 publications
(36 reference statements)
12
41
1
Order By: Relevance
“…From the results of attitude measurement on changing trends towards millet farming for future it could be observed that 57.50 percent of the respondents had positive attitude and completely agreed that millets are crops for future farming due to its present market potential and demand in urban markets. These findings were supported by the previous studies conducted by D'Silva, et al [13] Hu Y, et al [14] Arbiol, et al [15] which confirmed that, there was a positive relationship between attitude and the outcome variable adoption. This is followed by 31.67 per cent of the respondents who had neither positive nor negative attitude and stayed neutral.…”
Section: Administration Of the Scalesupporting
confidence: 87%
“…From the results of attitude measurement on changing trends towards millet farming for future it could be observed that 57.50 percent of the respondents had positive attitude and completely agreed that millets are crops for future farming due to its present market potential and demand in urban markets. These findings were supported by the previous studies conducted by D'Silva, et al [13] Hu Y, et al [14] Arbiol, et al [15] which confirmed that, there was a positive relationship between attitude and the outcome variable adoption. This is followed by 31.67 per cent of the respondents who had neither positive nor negative attitude and stayed neutral.…”
Section: Administration Of the Scalesupporting
confidence: 87%
“…The findings only 45.3% of the respondents answered that the infected person may have certain sign and symptoms. This results also similar among respondents from Philippines and Trinidad with 44% and 47% respectively [5], [18] but lower compared to Brazil with 68% [4]. This fact indicates that majority of people are not aware of the disease as most of infected persons are asymptomatic.…”
Section: B Knowledge Attitude and Practice (Kap) Scores Categorizedsupporting
confidence: 61%
“…The level of knowledge on mode of transmission and causes contributing to leptospirosis noted in this current study is better than the other factors. This finding is quite lower compared to those obtained by [4], [5], [19], [18]. This may imply that the respondents know the disease is caused by bacteria and it is related to rodents and its urine and how the microbes enter into the body.…”
Section: B Knowledge Attitude and Practice (Kap) Scores Categorizedcontrasting
confidence: 60%
See 2 more Smart Citations